Evaluation of an electronic nose for odorant and process monitoring of alkaline-stabilized biosolids production. (November 2017) - Romero-Flores, Adrian; McConnell, Laura L.; Hapeman, Cathleen J.; Ramirez, Mark; Torrents, Alba
Abstract: Electronic noses have been widely used in the food industry to monitor process performance and quality control, but use in wastewater and biosolids treatment has not been fully explored. Therefore, we examined the feasibility of an electronic nose to discriminate between treatment conditions of alkaline stabilized biosolids and compared its performance with quantitative analysis of key odorants. Seven lime treatments (0–30% w/w) were prepared and the resultant off-gas was monitored by GC-MS and by an electronic nose equipped with ten metal oxide sensors. A pattern recognition model was created using linear discriminant analysis (LDA) and principal component analysis (PCA) of the electronic nose data. In general, LDA performed better than PCA. LDA showed clear discrimination when single tests were evaluated, but when the full data set was included, discrimination between treatments was reduced. Frequency of accurate recognition was tested by three algorithms with Euclidan and Mahalanobis performing at 81% accuracy and discriminant function analysis at 70%. Concentrations of target compounds by GC-MS were in agreement with those reported in literature and helped to elucidate the behavior of the pattern recognition via comparison of individual sensor responses to different biosolids treatment conditions. Results indicated that the electronic nose can discriminate between lime percentages, thus providing the opportunity to create classes of under-dosed and over-dosed relative to regulatory requirements. Full scale application will require careful evaluation to maintain accuracy under variable process and environmental conditions. Highlights: Odorants in emissions from biosolids were analyzed by GCMS and the enose. The enose differentiated under dose from over dose alkaline stabilized biosolids. Small increase in calcium oxide dose was not differentiated by the electronic nose. Odorants monitoring by GCMS better differentiated process conditions.